A Comparison of in-vitro Pharmacokinetics and Pharmacodynamics of Branded and Its Locally Produced Cefuroxime Sodium Against Staphylococcus and Escherichia Escherichia coli - Du M; Sun T; Wang X; Chi X; Xiao Y (Drug Design, Development and Therapy)
Mengjiao Du,1,2,* Tingting Sun,1,2,* Xueting Wang,3,4 Xiaohui Chi,5 Yonghong Xiao2– 4 1Shandong First Medical University & Shandong Academy of Medical Sciences, Jinan, Shandong, People’s Republic of China; 2Jinan Microecological Biomedicine Shandong Laboratory, Jinan, Shandong, People’s Republic of China; 3Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, The First Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang, People’s Republic of China; 4Research Units of Infectious Disease and Microecology, Chinese Academy of Medical Sciences, Hangzhou, Zhejiang, People’s Republic of China; 5Department of Medical Laboratory, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaohui Chi, Department of Medical Laboratory, The Affiliated Yantai Yuhuangding Hospital of Qingdao University, Yantai, Shandong, People’s Republic of China, Email 15684003984@163.com Yonghong Xiao, Jinan Microecological Biomedicine Shandong Laboratory, Jinan, Shandong, People’s Republic of China, Email xiao-yonghong@163.comPurpose: To compare the in-vitro antibacterial effects of branded and its locally produced cefuroxime sodium against Staphylococcus ATCC29213, clinical strains of methicillin-sensitive Staphylococcus aureus (MSSA) 164342 and methicillin-sensitive coagulase-negative staphylococci (MSCNS) 117933, and Escherichia coli ATCC25922, and to provide a reference for their clinical use.Methods: An in-vitro antibacterial susceptibility test, time-kill curve and pharmacokinetics and pharmacodynamics (PK/PD) modeling was used in the comparison.Results: The minimum inhibitory concentrations (MIC) of the two types of cefuroxime sodium were identical against four bacterial strains; both types of cefuroxime sodium had MICs of 0.5 μg/mL, 8 μg/mL, 0.5 μg/mL, and 0.25 μg/mL against ATCC 29213, ATCC 25922, M164342 and MSCNS117933, respectively. There were no significant differences in the time-kill curves of the two forms against the four strains at three concentrations. At drug concentrations of 2×MIC and 4×MIC, the bacterial count of all the strains decreased from 6 log CFU/mL to around 4 log CFU/mL. The bactericidal efficacies of the two agents were generally similar in the pharmacokinetics model of simulated intravenous drug administration of 1 g q8h. Only the PD parameter of bactericidal rate (KR) for ATCC 29213 and the area difference between the drug bactericidal curve and the bacterial growth control curve (IE) for ATCC25922 were statistically different. The KR and IE of the locally produced form were 0.73± 0.10 logCFU·h/mL and 83.73± 12.69 logCFU·h/mL, respectively, while the KR and IE of the branded form were 1.19± 0.07 logCFU·h/mL and 104.02± 16.28 logCFU·h/mL, respectively.Conclusion: The in-vitro antibacterial effect of locally produced cefuroxime sodium against Staphylococci and E. coli is comparable to that of branded cefuroxime sodium.Keywords: cefuroxime sodium, pharmacokinetics/pharmacodynamics, time-kill curves, in vitro